Peningkatan Kualitas Produk Keripik Buah Apel di UMKM CV Andhini Kota Batu Malang - Daryono, Elvianto Dwi; Hudha, Mohammad Istnaeny (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
Batu Malang City is the largest apple producing area in East Java. The apples produced sometimes do not meet market specifications. UMKM CV. Andhini uses the apples as raw material for apple chips. The problem faced by UMKM is the high cost of electricity to freeze apples for 24 hours in the freezer before the apples are fried. In addition, there are also complaints about the price of coconut oil for frying apple chips. This community service program provides a solution by using a 2% concentration CaCl2 solution to soak apples for 40 minutes before frying. Expensive coconut oil is replaced with packaged oil which is a mixture of coconut oil and palm oil at a cheaper price. The two solutions produce crispy apple chips, evenly cooked and with a fragrant aroma like coconut oil. UMKM owners expressed satisfaction with the products produced. The problem of high electricity costs and high coconut oil prices can be overcome.